The tuberculosis vaccine H4:IC31 is safe and induces a persistent polyfunctional CD4 T cell response in South African adults: A randomized controlled trial. Issue 30 (9th July 2015) - Geldenhuys, Hennie; Mearns, Helen; Miles, David J.C.; Tameris, Michele; Hokey, David; Shi, Zhongkai; Bennett, Sean; Andersen, Peter; Kromann, Ingrid; Hoff, Søren T.; Hanekom, Willem A.; Mahomed, Hassan; et al.
Abstract: Background: New, more effective vaccines to prevent tuberculosis (TB) disease are needed urgently. H4:IC31 is an investigational vaccine that contains a fusion protein of the immunodominant antigens TB10.4 and Ag85B, formulated in IC31 ® adjuvant. We assessed the safety and immunogenicity of H4:IC31 in South African adults from a TB endemic setting. Methods: In this double blind, placebo controlled, phase I trial, Mycobacterium tuberculosis -uninfected, HIV-uninfected, healthy adults with a history of childhood BCG vaccination were randomly allocated to two intramuscular vaccinations with 5, 15, 50 or 150 μg H4 formulated in 500 nmol IC31 ®, two months apart. Vaccinees were followed for six months to assess safety; immunogenicity was measured by ELISpot and intracellular cytokine staining assays. Results: Thirty-two participants received H4:IC31 and 8 received placebo. Injection site adverse events were common but mild; mild fatigue was the most common systemic adverse event. Frequencies of adverse events did not differ between dosage groups. Detectable antigen-specific CD4 T cell responses were induced by all doses of H4:IC31, but doses below 50 μg induced the highest frequencies of CD4 T cells, comprised predominantly of IFN-γ + TNF-α + IL-2 + or TNF-α + IL-2 + cells. These memory responses persisted up to the end of follow up, on study day 182. Conclusions: H4:IC31 demonstrated an acceptable safety profile and was immunogenic in South African adults. In this trial, the 15 μg dose appeared to induce the most optimal immune response.